2009
DOI: 10.1128/jb.00909-09
|View full text |Cite
|
Sign up to set email alerts
|

A Collagen-Binding Adhesin, Acb, and Ten Other Putative MSCRAMM and Pilus Family Proteins of Streptococcus gallolyticus subsp. gallolyticus ( Streptococcus bovis Group, Biotype I)

Abstract: Members of the Streptococcus bovis group are important causes of endocarditis. However, factors associated with their pathogenicity, such as adhesins, remain uncharacterized. We recently demonstrated that endocarditis-derived Streptococcus gallolyticus subsp. gallolyticus isolates frequently adhere to extracellular matrix (ECM) proteins. Here, we generated a draft genome sequence of an ECM protein-adherent S. gallolyticus subsp. gallolyticus strain and found, by genome-wide analyses, 11 predicted LPXTG-type ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 76 publications
(95 reference statements)
4
79
0
Order By: Relevance
“…In S. gallolyticus UCN34, two of these pilus operons express a protein similar to collagen binding proteins (Gallo_1570 and Gallo_2179), predicted to be adhesins. Similarly, it was recently described for S. gallolyticus strain TX20005 that it encodes three pilus operons and also collagen binding proteins (54). The locus gallo_2179-2177 is identical to the acb locus of strain TX20005, and the locus gallo_2040-2038 is identical to the sbs15 locus.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In S. gallolyticus UCN34, two of these pilus operons express a protein similar to collagen binding proteins (Gallo_1570 and Gallo_2179), predicted to be adhesins. Similarly, it was recently described for S. gallolyticus strain TX20005 that it encodes three pilus operons and also collagen binding proteins (54). The locus gallo_2179-2177 is identical to the acb locus of strain TX20005, and the locus gallo_2040-2038 is identical to the sbs15 locus.…”
Section: Resultsmentioning
confidence: 80%
“…S. gallolyticus isolates responsible for endocarditis exhibited heterogeneous patterns of adherence to extracellular matrix (ECM) proteins, which suggests that they produce different surface components (55). Recently, a collagen binding adhesin together with 10 putative ECM binding proteins were identified in the draft genome sequence of a human isolate of S. gallolyticus (54).…”
mentioning
confidence: 99%
“…gallolyticus subsp. gallolyticus, a commensal of the gastrointestinal tract, is found in 2.5 to 15% of healthy humans (2). The organism can also act as a pathogen.…”
mentioning
confidence: 99%
“…However, their ability to adhere to and colonize host tissues is largely unknown. It was found that S. bovis/gallolyticus bacteria possess collagenbinding proteins and pili that are responsible for adhesion to colorectal mucosa as well as to endocardium (Sillanpaa et al, 2009). On the other hand, another study (Boleij et al, 2009b) found a histone-like protein A on the surface of S. bovis/gallolyticus able to bind heparan sulfate proteoglycans at the colon tumor cell surface during the first stages of infection; this cell surface protein in S. gallolyticus acts as one of the main heparin-binding proteins that is largely responsible for bacteria selective adhesive potential as well as entry to the blood circulation.…”
Section: Clues For Etiological Rolementioning
confidence: 99%